2022
DOI: 10.3390/cells11020195
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphorus Flame Retardant TDCPP Displays Genotoxic and Carcinogenic Risks in Human Liver Cells

Abstract: Tris(1,3-Dichloro-2-propyl)phosphate (TDCPP) is an organophosphorus flame retardant (OPFR) widely used in a variety of consumer products (plastics, furniture, paints, foams, and electronics). Scientific evidence has affirmed the toxicological effects of TDCPP in in vitro and in vivo test models; however, its genotoxicity and carcinogenic effects in human cells are still obscure. Herein, we present genotoxic and carcinogenic properties of TDCPP in human liver cells (HepG2). 3-(4,5-Dimethylthiazol-2-yl)-2,5-diph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…However, our results could not clarify whether these associations are attributed to the diseases themselves or the medications used. TBEP was detected in dust from solid waste, e-waste dumpling sites, landfills, and wastewater treatment facilities (42). Previous studies from Japan revealed that TBEP was the most prevalent OPFRs in houses (43,44).…”
Section: Discussionmentioning
confidence: 95%
“…However, our results could not clarify whether these associations are attributed to the diseases themselves or the medications used. TBEP was detected in dust from solid waste, e-waste dumpling sites, landfills, and wastewater treatment facilities (42). Previous studies from Japan revealed that TBEP was the most prevalent OPFRs in houses (43,44).…”
Section: Discussionmentioning
confidence: 95%
“…Toxicological studies on TDCIPP mainly focused on its endocrine disruption, neurological disorders, reproductive and developmental toxicology, as well as its potential carcinogenicity (Chen et al, 2020; Li et al, 2017; Moser et al, 2015; Rhyu et al, 2019; Saquib et al, 2022). For example, Chen et al reported TDCIPP-induced reduction of sperm motility with no obvious changes in hormone levels (Chen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Rhyu et al, TDCIPP was found to cause abnormal tail fins in zebrafish embryos, which was associated with the altered expression of transcription factors involved in tail fin development (Rhyu et al, 2019). In addition, TDCIPP was shown to elicit genotoxic and carcinogenic risks in liver cells (Saquib et al, 2022). As a result, the risk of TDCIPP to human health cannot be neglected.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, emerging evidence suggests that TDCPP exposure can cause neurological, reproductive, endocrine, hepatic and renal damage [ 1 , 8 , 9 ]. Notably, it was listed as a known carcinogen on the Proposition 65 list of substances [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%